Fabrication of (Ba, Na)Fe2As2 round wires using HIP process. (September 2019) - Miyawaki, D; Pyon, S; Tamegai, T; Awaji, S; Takano, K; Kajitani, H; Koizumi, N
Abstract: We have fabricated round wires of Baa0.6 Na0.4 Fe2 As2 using powder-in-tube technique and hot isostatic press (HIP) treatment. Transport J c was measured at 4.2 K of two Ba0.6 Na0.4 Fe2 As2 round wires with Ag/Cu double sheath which were processed at 700 °C for 4 h at 175 MPa. Transport J c of one of the wires reached 76 kA/cm 2 and 24 kA/cm 2 at self-field and 100 kOe, respectively, while J c of another wire is slightly larger at low fields. It means that J c of Ba0.6 Na0.4 Fe2 As2 wire is resilient against large magnetic field, which demonstrates very promising characteristics of this material. Detailed characterizations of wires using X-ray diffraction and compositional mapping by EDX are also presented. We also explore the better condition for synthesis of Ba0.6 Na0.4 Fe2 As2 by changing the reaction temperature.